PENGENALAN KARAKTERISTIK KEWIRAUSAHAAN BAGI SISWA/I SMA - Mei Ie; Atalya Fransiska (PROSIDING SERINA, 2021)
Quality human resources are the most important and most important thing needed by a country for its economic development, especially the younger generation. Human resource development can be done through educational facilities. One of the education needed by the younger generation is entrepreneurship education. Through entrepreneurship education, students will be able to recognize and understand not only the value and knowledge of entrepreneurship, but also the characteristics of entrepreneurship. Which, the characteristics of entrepreneurship are not something that can be owned by every individual in general. But only individuals who have my entrepreneurial thoughts and behavior have them. So it can be interpreted that the characteristics of entrepreneurship are still not widely known by the younger generation. So the government is trying to commit to introducing the characteristics of entrepreneurship through educational facilities. The sooner the younger generation recognizes and even has entrepreneurial characteristics, the better the quality of Indonesian human resources. know themselves and others through brain color measurement. Which through this test students can know and understand themselves, even others more deeply. This brain color measurement is used to measure the entrepreneurial characteristics of students.